1998
DOI: 10.1016/s0016-7037(98)00243-9
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic iron mineralization accompanying the dissimilatory reduction of hydrous ferric oxide by a groundwater bacterium

Abstract: Dissimilatory iron-reducing bacteria (DIRB) couple the oxidation of organic matter or H 2 to the reduction of iron oxides. The factors controlling the rate and extent of these reduction reactions and the resulting solid phases are complex and poorly understood. Batch experiments were conducted with amorphous hydrous ferric oxide (HFO) and the DIRB Shewanella putrefaciens, strain CN32, in well-defined aqueous solutions to investigate the reduction of HFO and formation of biogenic Fe(II) minerals. Lactate-HFO so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
730
6
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(796 citation statements)
references
References 81 publications
56
730
6
4
Order By: Relevance
“…Magnetite and vivianite formation by S. putrefaciens CN32 has been reported by several researchers (Bell et al, 1987;Kostka and Luther, 1995;Roden and Zachara, 1996;Fredrickson et al, 1998;Dong et al, 2000;O'Loughlin et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Magnetite and vivianite formation by S. putrefaciens CN32 has been reported by several researchers (Bell et al, 1987;Kostka and Luther, 1995;Roden and Zachara, 1996;Fredrickson et al, 1998;Dong et al, 2000;O'Loughlin et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
“…The biostimulation of DMRB will likely lead to biological Fe(III) reduction (Wielinga et al, 2000;Finneran et al, 2002;Anderson et al, 2003;Elias et al, 2004;) and production of sorbed Fe(II) or Fe(II)-bearing minerals as metabolic products. The Fe(II)-bearing phases found include magnetite, siderite, vivianite, ferruginous smectite, and green rust (Bell et al, 1987;Roden and Zachara, 1996;Fredrickson et al, 1998;Zachara et al, 1998;Dong et al, 2000;Roh et al, 2003;O'Loughlin et al, 2007;Komlos et al, 2008;O'Loughlin et al, 2010). Sorbed Fe(II) and the Fe(II)-bearing biogenic phases can provide a reservoir of reducing capacity where reduction of U(VI) may occur due to abiotic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Strain CN32, isolated from anaerobic groundwater, is capable of carrying out dissimilatory Fe(III) reduction with either lactate or H2 as an electron donor. As previously described (15), the cells were grown aerobically for 16 h on tryptic soy broth (TSB) and then washed twice with sterile anaerobic PIPES buffer prior to use in Fe(III) oxide reduction experiments. The tubes were incubated at room temperature on a rotary shaker (150 rpm) for 3 d. Subsamples were removed daily with a N2-flushed plastic syringe and 18G needle and analyzed for dissolved (0.2 µm-filtered) and total (0.5 M HClextractable) Fe(II) content by Ferrozine analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Since most members of group 2 were from the genus Shewanella, we expressed DPP (MEROPS ID: MER096825) from S. putrefaciens to determine the peptidase activity of these members carrying Ser 673 . S. putrefaciens is a typical species of the genus that has been isolated mostly from fish, poultry, and meats, but is also associated with a broad range of human infections [34,35]. It was found that S. putrefaciens DPP specifically cleaved Leu-Asp-and Leu-Glu-MCA, demonstrating its entity as DPP11 (Fig.…”
Section: Dpp From the Phylum Proteobacteria And Expression Of Shewanementioning
confidence: 99%